Pathogenesis of myonecrosis induced by coral snake (Micrurus nigrocinctus) venom in mice - Gutiérrez, José María (1986)
The mode by which coral snake (Micrurus nigrocinctus) venom affects skeletal muscle was studied using a combined approach. The venom induced early functional and structural alterations in the plasma membrane of muscle cells, suggesting that sarcolemma is the primary site of action of this venom. This was shown by the presence of wedge-shaped ('delta') lesions at the periphery of the cells, as well as by focal disruptions in the continuity of plasma membrane as early as 1 5 min after envenomation. After this initial alteration the rest of the organelles were severely affected. Myofilaments were hypercontracted leaving, as a consequence, areas of overstretched myofibrils as well as empty spaces. Eventually, myofilaments formed dense, clumped masses in which the striated structure was totally lost. At 24 h, myofilaments were still disorganized but they presented a more hyaline and homogeneous appearance. As early as 1 5 and 30 min mitochondria were swollen; later, by 1, 3 and 24 h, they showed further alterations such as the presence of dense intracristal spaces and vesiculated cristae, as well as disruption in the integrity of their membranes. Sarcoplasmic reticulum was dilated and disorganized into many small vesicles randomly distributed throughout the cellular space. Moreover, the venom induced a rapid decrease in muscle levels of creatine and creatine-kinase (CK) and a calcium influx. Since the rates of efflux of creatine and CK were similar, it is suggested that the lesions produced in the membrane are large enough to allow the escape of these two molecules. As corroboration of the severe myotoxic effect, envenomated mice excreted reddish urine containing large quantities of myoglobin. Skeletal muscle cells are more susceptible to the action of the venom than erythrocytes, since coral snake venom induced only a mild direct haemolytic effect in vitro and haemolysis is not a significant effect in vivo. M. nigrocinctus venom induced a drastic increase in plasma levels of lactate dehydrogenase. Isozymes LDH-3, LDH-4, and LDH-5 increased markedly, suggesting that the systemic pathology of coral snake envenoming may be more complex than previously thought.